Why do startups fail? A core competency deficit model - Szathmári, Edit; Varga, Zoltán; Molnár, Attila; Németh, Gergely; Szabó, Zsolt Péter; Kiss, Orhidea Edith (Frontiers in Psychology, 2024)
A growing body of work aims to explore the reasons behind startup failures. However, there is a need for integrative approaches organized around conceptual frameworks to avoid fragmented and perplexing knowledge about these reasons. To our knowledge, no previous research has systematically investigated the role of competency deficits in startup failures, a crucial element of these failures. In our study, we adapted Spencer's behavioral competence model specifically for startups to identify the competencies within startup teams that, according to their Chief Executive Officers, contributed to their downfall. Three coders meticulously analyzed 50 online accounts of startup failures using a modified Critical Incident Technique. This analysis revealed two prominent competency deficits as pivotal determinants of these startups' outcomes: information-seeking and customer service orientation. Additionally, deficits in technical expertise, analytical thinking, and flexibility emerged as significant factors contributing to these failures. The competency deficits identified in this study offer focal points for evaluating and enhancing startup teams, thereby helping to prevent failure.